Protective Effects of Baicalin on Peritoneal Tight Junctions in Piglets Challenged with Glaesserella parasuis - Zhang, Jiacheng (Molecules, 2021)
Glaesserella parasuis (G. parasuis) causes inflammation and damage to piglets. Whether polyserositis caused by G. parasuis is due to tight junctions damage and the protective effect of baicalin on it have not been examined. Therefore, this study aims to investigate the effects of baicalin on peritoneal tight junctions of piglets challenged with G. parasuis and its underlying molecular mechanisms. Piglets were challenged with G. parasuis and treated with or without baicalin. RT-PCR was performed to examine the expression of peritoneal tight junctions genes. Immunofluorescence was carried out to detect the distribution patterns of tight junctions proteins. Western blot assays were carried out to determine the involved signaling pathways. Our data showed that G. parasuis infection can down-regulate the tight junctions expression and disrupt the distribution of tight junctions proteins. Baicalin can alleviate the down-regulation of tight junctions mRNA in peritoneum, prevent the abnormalities and maintain the continuous organization of tight junctions. Our results provide novel evidence to support that baicalin has the capacity to protect peritoneal tight junctions from G. parasuis-induced inflammation. The protective mechanisms of baicalin could be associated with inhibition of the activation of PKC and MLCK/MLC signaling pathway. Taken together, these data demonstrated that baicalin is a promising natural agent for the prevention and treatment of G. parasuis infection.